Influence of forest magrove on increased deposition rate and wave attenuation in Ngoc Hai area (Hai Phong) - Thai, Vu Doan (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 1, 2012)
Abstract. Mangrove forests in Hai Phong coastal area are the ecosystem with high productivity. Mangroves forests also have a good role on protection dike and coastal residential area. The extending of alluvial deposition area and development of mangrove forest are two processes occur together. Base on the results study on the coastal zone of Ngoc Hai (Do Son, Hai Phong) since 2004 to 2011, this paper shown the role of mangrove forest on increased deposition rate, heighten bathymetry, and wave attenuation in Ngoc Hai area (Hai Phong). Deposition rate in the study could be increased about 0.1-0.4cm/year if mangroves age increasing one year age.